Improving the Institutional Base of the Business Environment - Mukhitdinov, Shukhrat Z.; Bayboboeva, Firuza N. (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
The article highlights that the need to ensure the economic security of small business is not only reflected in the impact of the crisis, but also in the interests of economic threats, possible losses and damages to competitors and the risk of a crisis.